Language Policy and the Pursuit of a New Linguistic Identity in Morocco: A Critical Analysis of Pro-English Discourse on Twitter - Elbourkhissi, Lhou; Houssaini, Khalid (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Morocco’s sociolinguistic landscape has been shaped by enduring historical, political, and ideological forces that continue to structure public discourse on language policy. Moroccan language policy has fluctuated between the unassailable dominance of French in economic, educational and political domains and Arabisation initiatives to reinstate Arabic as the language of national identity. Recently, online campaigns, particularly on social media platforms like Twitter, called for the displacement of French in favour of English as the primary foreign language in the country. Drawing on a corpus of tweets posted between 1 September 2021 and March 2023, this paper uses corpus-assisted discourse studies to examine language ideologies articulated in Arabic, English, French, and Tamazight posts. Findings reveal that English, on one hand, is framed as a language of global opportunity, related to scientific advancement, professional mobility, and cultural modernity. On the other hand, French is portrayed as a colonial remnant, indicative of restricted economic horizons and historical inequality. Concurrently, Arabic and Tamazight emerge in the data not only as symbols of national identity but also as ideological anchors, invoked by some users to advocate for linguistic sovereignty. However, these official languages remain discursively marginal concerning science, technology, and international communication. This paper sheds light on the digital negotiation of Morocco’s linguistic future, where public discourse blurs the boundaries between language policy, colonial past, economic aspirations, and globalisation. By tracing these discursive struggles, this study adds substantially to the understanding of the evolving role of social media in shaping language planning and language ideologies.